Lipoxin formation during human neutrophil-platelet interactions. Evidence for the transformation of leukotriene A4 by platelet 12-lipoxygenase in vitro. - Serhan, C N (1990)
Human neutrophils from peripheral blood may physically interact with platelets in several settings including hemostasis, inflammation, and a variety of vascular disorders. A role for lipoxygenase (LO)-derived products has been implicated in each of these events; therefore, we investigated the formation of lipoxins during coincubation of human neutrophils and platelets. Simultaneous addition of FMLP and thrombin to coincubations of these cells led to formation of both lipoxin A4 and lipoxin B4, which were monitored by reversed-phase high pressure liquid chromatography. Neither stimulus nor cell type alone induced the formation of these products. When leukotriene A4 (LTA4), a candidate for the transmitting signal, was added to platelets, lipoxins were formed. In cell-free 100,000 g supernatants of platelet lysates, which displayed 12-LO activity, LTA4 was also transformed to lipoxins. Platelet formation of lipoxins was inhibited by the LO inhibitor esculetin and partially sensitive to chelation of Ca2+, while neither acetylsalicylic acid nor indomethacin significantly inhibited their generation. In contrast, neutrophils did not transform LTA4 to lipoxins. Cell-free 100,000 g supernatants of neutrophil lysates converted LTA4 to LTB4. These results indicate that neutrophil-platelet interactions can lead to the formation of lipoxins from endogenous sources and provide a role for platelet 12-LO in the formation of lipoxins from LTA4.